The Faith Journey of the Royal Official from Capernaum in Jn 4:43-54 - Nalewaj, Aleksandra (Studia Warmińskie, 2024)
The purpose of this study is to attempt to show the faith process of the royal official from Capernaum in the light of Jn 4:43-54. The article consists of three parts. The first part focuses on literary issues such as the separation of the pericope Jn 4:43-54 from the larger literary section and its place in the current Gospel setting, the context of the story and the literary structure. The second section takes a closer look at the profile of a possibly pagan courtier, while the third illustrates his journey of faith in Jesus. The anonymous official who, without seeing signs and wonders, believed in the healing power of Jesus' word at a distance appears as a model of faith.